How fear of intimacy affects infertile men’s neuropsychological functioning through mental toughness - Hassan, Sajid; Bhatti, Mazhar Iqbal; Habib, Shazia; Fatima, Sidra; Bhader, Sher; Khan, Nazeer Hussain; Jiang, Enshe (Frontiers in Psychiatry, 2023)
There is a significant need in Pakistan to investigate the psychological effects of infertility on the mental health of infertile men. The current study examined how fear of intimacy affects neuropsychological impairment and evaluated its relationship to other variables including quality of life and mental toughness. An analytical cross-sectional study was carried out on infertile male patients in various healthcare settings in Punjab, Pakistan. The participants were recruited using a non-probability (purposive) sampling strategy. The sample size was 120 infertile. SPSS 26 was used to analyze the data. The fear of intimacy scale, neuropsychological Impairment scale, QoL scale (WHOQOl-BREF), and Mental Toughness Questionnaire were used to assess the mental health of infertile patients, respectively. Fear of intimacy was found to have a significant impact on neuropsychological impairment (r = .40; **p < 0.01) as well as a negative impact on QoL (r = − .25; *p > 0.05). Similarly, neuropsychological impairment was found to be negatively associated to QoL (r = − .52; **p > 0.01). The relationship between fear of intimacy and neuropsychological impairment was found to be significantly mediated by QoL. Furthermore, the findings revealed that mental toughness significantly moderated the relationship between fear of intimacy and neuropsychological impairment. Overall, infertile men in Pakistan had relatively high levels of fear of intimacy, which largely caused neuropsychological impairment. Fear of intimacy and neuropsychological impairment significantly disturb infertile men’s quality of life. The impact of fear of intimacy on neuropsychological impairment dropped significantly as mental toughness enhanced. This article can help neuropsychological researchers, mental health professionals, as well as policymakers in improving clinical mental health practices for infertile patients.